2017
DOI: 10.1002/lary.27001
|View full text |Cite
|
Sign up to set email alerts
|

Minimal clinically important difference of voice handicap index‐10 in vocal fold paralysis

Abstract: 4. Laryngoscope, 128:1419-1424, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 45 publications
(185 reference statements)
4
43
2
Order By: Relevance
“…In patients with vocal fold paralysis, an improvement of 4 points on the VHI-10 scale has been suggested to be the minimal clinically important difference that results in a perceivable voice change. 16 Misono et al also reported on patients with a variety of vocal fold disorders and found that the minimal important difference on the VHI-10 scale was 6 points. 17 Currently, these are the only reference values to indicate a clinically significant voice improvement that is notable by patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In patients with vocal fold paralysis, an improvement of 4 points on the VHI-10 scale has been suggested to be the minimal clinically important difference that results in a perceivable voice change. 16 Misono et al also reported on patients with a variety of vocal fold disorders and found that the minimal important difference on the VHI-10 scale was 6 points. 17 Currently, these are the only reference values to indicate a clinically significant voice improvement that is notable by patients.…”
Section: Discussionmentioning
confidence: 98%
“…Even at the point of lowest/best VHI‐10 score, the patients in the ML group still reported better voice outcomes. In patients with vocal fold paralysis, an improvement of 4 points on the VHI‐10 scale has been suggested to be the minimal clinically important difference that results in a perceivable voice change . Misono et al also reported on patients with a variety of vocal fold disorders and found that the minimal important difference on the VHI‐10 scale was 6 points .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our result is qualitatively consistent with what has been previously found for other validated patient‐reported outcome measures. Previous studies of other validated (otolaryngic and non‐otolaryngic) patient‐reported outcome measures have reported sensitivities in the range of 50‐60% for MCID estimates in detecting patients reporting noticeably improved outcomes …”
Section: Discussionmentioning
confidence: 99%
“…The total score is used to indicate the severity of the voice disorders for the patient. Higher scores indicate that a voice problem has a more severe handicapping effect on the individual’s life than a lower score [ 12 14 ]. Maximum phonation time (MPT) is also a clinical tool for assessing phonatory mechanics.…”
Section: Methodsmentioning
confidence: 99%